Response by Prof. Joop Evers - Evers, Joseph J.M. (European Journal of Transport and Infrastructure Research, 2007)
The remarks by professor Weidmann concern: (1) Trip booking (discussed in III); The unmanageable number of O/D-relations (discussed in I); (2) Relations with other PTmodalities (discussed in II); (3) Capacity (see I and Profile paper: ‘State of art of fast transport by buses’); (4) Political feasibility (discussed in V and VI); (5) Speed (discussed in II) and (6) Infrastructure (discussed in II, VI and VII). The remarks of professor Bookhuis concern: (1) FTR as an alternative for car travelling (discussed in IV) and (2) Opportunities (discussed in VII). The author thanks professor Brookhuis and professor Weidmann for their interesting and stimulating remarks.